R-carvedilol, a potential new therapy for Alzheimer’s disease - Yao, Jinjing; Chen, S. R. Wayne (Frontiers in Pharmacology, 2022)
The amyloid cascade hypothesis has dominated the field of Alzheimer’s disease (AD) research, drug development, and clinical trials for decades. However, a growing body of evidence indicates that simply removing amyloid plaques may not significantly affect AD progression. Alternatively, it has been proposed that AD progression is driven by increased neuronal excitability. Consistent with this alternative hypothesis, recent studies showed that pharmacologically limiting ryanodine receptor 2 (RyR2) open time with the R-carvedilol enantiomer prevented and rescued neuronal hyperactivity, memory impairment, and neuron loss in AD mouse models without affecting the accumulation of β-amyloid (Aβ). These data suggest that R-carvedilol may represent a potential new therapy for AD.